Lung adenocarcinoma and anti‐transcriptional intermediary factor 1‐gamma positive dermatomyositis complicated with spontaneous oesophageal rupture. Issue 3 (4th February 2019) - Saraya, Takeshi; Tamura, Masaki; Kasuga, Keisuke; Fujiwara, Masachika; Takizawa, Hajime
Abstract : A 58‐year‐old man presented with a two‐month history of facial erythema and dry cough. Physical examination revealed typical cutaneous manifestations of dermatomyositis (DM), including heliotrope rash and shawl sign. A chest X‐ray revealed a 4‐cm mass in the right middle lung. After bronchoscopy and investigation of auto‐antibodies, he was diagnosed with co‐occurring transcriptional intermediary factor 1‐gamma (TIF1‐γ) positive DM and lung adenocarcinoma. He was administered oral prednisolone for subsequent muscle weakness, but developed TIF1‐γ positive DM‐associated oropharyngeal dysphagia complicated by spontaneous oesophageal rupture and died from progression of chemoresistant lung cancer. Abstract : A 58‐year‐old man presented with a two‐month history of facial erythema and dry cough. After testing he was diagnosed with co‐occurring transcriptional intermediary factor 1‐gamma (TIF1‐γ) positive dermatomyositis (DM) and lung adenocarcinoma. He subsequently developed muscle weakness and was administered oral prednisolone but developed TIF1‐γ positive DM‐associated oropharyngeal dysphagia complicated by spontaneous oesophageal rupture. Despite treatment, he gradually deteriorated and died from progression of chemoresistant lung cancer six months later.